Comparison of five commercially available immunochromatographic tests for the detection of norovirus in faecal specimens. Issue 2 (October 2015) - Vyas, K.; Atkinson, C.; Clark, D.A.; Irish, D.
Summary Five CE-marked immunochromatography assay kits for the rapid detection of norovirus were compared with the reference method of real-time polymerase chain reaction (PCR) for the detection of acute norovirus infection. The sensitivity of the assays ranged between 23% and 59% with specificity being 75‒100% when compared with real-time PCR. The data suggest that a reactive immunochromatographic assay indicates norovirus infection. However, the sensitivity of the assay would need to be significantly improved to be suitable for routine diagnostic purposes or as an alternative to laboratory analysis for near-patient testing.